2010
DOI: 10.1073/pnas.1003852107
|View full text |Cite
|
Sign up to set email alerts
|

Th17 plasticity in human autoimmune arthritis is driven by the inflammatory environment

Abstract: In several murine models of autoimmune arthritis, Th17 cells are the dominant initiators of inflammation. In human arthritis the majority of IL-17–secreting cells within the joint express a cytokine phenotype intermediate between Th17 and Th1. Here we show that Th17/1 cells from the joints of children with inflammatory arthritis express high levels of both Th17 and Th1 lineage-specific transcription factors, RORC2 and T-bet. Modeling the generation of Th17/1 in vitro, we show that Th17 cells “convert” to Th17/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
356
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 386 publications
(423 citation statements)
references
References 40 publications
37
356
1
4
Order By: Relevance
“…A similar conclusion was also obtained in humans; Nistala et al (36) showed Th17 to Th1 plasticity driven by the inflammatory environment in patients with autoimmune polyarthritis. Likewise, we have found an accumulation of CD4+ CD161+ T cells able to produce IFN-c (Th1), or both IFN-c and IL-17A (Th17/Th1), but not IL-17A alone (Th17), in the synovial fluid (SF) of children with oligoarticular juvenile idiopathic arthritis (JIA) (37).…”
Section: The Discovery Of Th17 Cells In Mice and Humanssupporting
confidence: 63%
“…A similar conclusion was also obtained in humans; Nistala et al (36) showed Th17 to Th1 plasticity driven by the inflammatory environment in patients with autoimmune polyarthritis. Likewise, we have found an accumulation of CD4+ CD161+ T cells able to produce IFN-c (Th1), or both IFN-c and IL-17A (Th17/Th1), but not IL-17A alone (Th17), in the synovial fluid (SF) of children with oligoarticular juvenile idiopathic arthritis (JIA) (37).…”
Section: The Discovery Of Th17 Cells In Mice and Humanssupporting
confidence: 63%
“…Another possibility is that Th1 cells may convert to Th17 cells or to an intermediate Th17/Th1 phenotype, which has been previously observed in patients with arthritis and in mice with experimental autoimmune encephalomyelitis (45,46). Regardless of the mechanisms leading to the shift from a primarily IFN␥ response early to a higher Th17/Th1 response later, we nevertheless observed that the frequencies and numbers of IL-17A-and IFN␥-producing CD4ϩ T cells were reduced in the inflamed paws of CXCR6 Ϫ/Ϫ mice compared to arthritic wild-type mice, providing one explanation for the reduced severity of arthritis in CXCR6 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, some studies, especially in autoimmune diseases, proposed that the Th17 phenotype is unstable and that Th17 cells may convert to Th1 cells. 26 We can suggest that in a context of gastrointestinal aGVHD, some Th17 cells infiltrate early the intestinal mucosa and then can differentiate into Th1 cells making their detection more difficult if intestinal biopsies are performed too late after the onset of aGVHD. Recently, Esplugues et al 27 proposed a general mechanism for controlling immunopathogenic Th17 response by acquisition of an immune-suppressive phenotype or elimination into the intestinal lumen.…”
Section: Th17 and Plasmacytoid Dendritic Cells In Agvhd C Bossard Et Almentioning
confidence: 99%